Caracterização da ação da saliva do carrapato Amblyomma cajennense (Acari; Ixodidae) sobre a via clássica do sistema complemento - Paula Ferreira Franco (2015)
Ticks are a major concern in human and veterinary medicine because they cause blood loss and transmit several pathogens to their hosts. The activity performed by molecules produced by the salivary gland and gut of these arthropods are crucial for them to obtain blood and reach reproductive success. Among various activities performed by saliva, the inhibition of the complement system is important by delaying an immune response against salivary proteins and protecting the intestinal epithelium from the complement system, present within the ingested blood. The overall objective of this study was to characterize the anticomplement activity of Amblyomma cajennense saliva on the classical pathway of the human complement system. We evaluated whether the saliva and EGS from partially engorged and engorged ticks after different days of feeding are capable of inhibiting the action of the complement system. For this, hemolysis assays were performed with sheep red blood cells and human serum to evaluate the action in the classical pathway. We also measured the female A. cajennenses intestinal pH and the efficiency of the human complement system atthis pH. The results showed that both the saliva and EGS are able to inhibit the classical pathway hemolysis of human complement system, but the tick saliva was more effective than the EGS. The EGS of partially engorged and engorged ticks inhibit hemolysis, with extracts from engorged ticks being more effective. The EGS from A. cajennense fed to mice, presented greater inhibition of the classical pathway when dissected towards the end of the feeding stage (last 48 hours during feeding) and the activity showed a significant positive correlation (r = 0.585, p <0.001) with total weight, unlike EGS obtained from ticks fed on horses, where the inhibition is equal in ticks of different weights. The pH found in the A. cajennenses gut was 8.04 and the adjustments of the haemolytical assays to alkaline conditions did not interfere with classical pathway activation and the role of complement inhibitors, with the most effective inhibition occurring at pH 7.0. The knowledge of when these inhibitors are expressed in tick saliva and how they act may be used in future experiments searching new methods of tick control.